2015
DOI: 10.1155/2015/671094
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Individual Variations in Autonomic Responses to Urban and Forest Environments

Abstract: Autonomic responses to urban and forest environments were studied in 625 young male subjects. The experimental sites were 57 forests and 57 urban areas across Japan. The subjects viewed the landscape (forest or urban environment) for a period of 15 min while sitting on a chair. During this period, heart rate variability (HRV) was monitored continuously. The results were presented as histograms and analyzed with special reference to individual variations. Approximately 80% of the subjects showed an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 32 publications
6
58
1
Order By: Relevance
“…Olfactory stimulation by Japanese cypress leaf oil and inhalation of D-limonene enhanced parasympathetic nervous activity by 34.5 and 26.4 %, respectively, compared with a control (air) [5,6]; these findings were in accordance with the results of our previous laboratory experiments [17,18]. In our forest therapy field experiment, which included a large sample size of 625 participants [19], 79.2 % of the participants showed an increase in parasympathetic nervous activity in a forest environment compared with that in an urban environment. However, only 63.5 % of the participants exhibited decreases in sympathetic nervous activity [19].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Olfactory stimulation by Japanese cypress leaf oil and inhalation of D-limonene enhanced parasympathetic nervous activity by 34.5 and 26.4 %, respectively, compared with a control (air) [5,6]; these findings were in accordance with the results of our previous laboratory experiments [17,18]. In our forest therapy field experiment, which included a large sample size of 625 participants [19], 79.2 % of the participants showed an increase in parasympathetic nervous activity in a forest environment compared with that in an urban environment. However, only 63.5 % of the participants exhibited decreases in sympathetic nervous activity [19].…”
Section: Resultssupporting
confidence: 89%
“…In our forest therapy field experiment, which included a large sample size of 625 participants [19], 79.2 % of the participants showed an increase in parasympathetic nervous activity in a forest environment compared with that in an urban environment. However, only 63.5 % of the participants exhibited decreases in sympathetic nervous activity [19]. Based on these findings, we concluded that the parasympathetic nervous activity index of HRV was more sensitive than the sympathetic nervous activity index.…”
Section: Resultsmentioning
confidence: 99%
“…However, the benefits of forest-walking are not only psychological. Other studies have shown that it has desirable effects on physiological functions as well, including decreased blood pressure (8)(9)(10)(11), increased high-frequency component (HF) of heart rate variability (HRV) (12)(13)(14)(15), decreased cerebral activity (16), and enhanced immune functions (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research using newly developed indices such as the Perceived Restorativeness Scale (PRS; Korpela and Hartig 1996;Hartig et al 1997a;Hartig et al 1997b), the Restorative Outcome Scale (ROS; Korpela et al 2008;Korpela et al 2010), and the Subjective Vitality Scale (SVS; Ryan and Frederick 1997) has shown that forest bathing results in psychological restoration and improved vigor (Takayama and Kagawa 2013;Takayama, Korpela, Lee et al 2014b;Tyrväinen et al 2014). Furthermore, Kobayashi et al (2015) performed a large-scale field experiment throughout Japan in 60 forests known as "therapy bases" maintained for forest bathing. Finally, a few notable studies have confirmed the considerable physiological and psychological effects not only of remote forests but also of urban forests (Tsunetsugu et al 2013;Tyrväinen et al 2014b).…”
Section: Introductionmentioning
confidence: 99%